2022
DOI: 10.1111/dth.15935
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional combined furosemide and digoxin in cutaneous warts treatment: A randomized controlled clinical trial

Abstract: Although being a benign lesion, Warts can affect the quality of life by causing discomfort, disfigurement, and social embarrassment besides the tendency to spread.Cutaneous wart treatment faces many challenges as the development of an antiviral drug that can eradicate the human papilloma virus (HPV) is difficult. This clinical study aimed to assess the efficacy and safety of intralesional combined furosemide and digoxin in the treatment of multiple cutaneous warts. This double blinded randomized clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…This may be due to their scoring system, as they considered excellent response if there was 75–100% decrease in wart size as compared to a full disappearance (100%) in our study. Furthermore, it was much lower than other studies that reported more than 90% clearance [ 15 ]. This can be elucidated by the dissimilar concentration of the combined drugs.…”
Section: Discussioncontrasting
confidence: 55%
“…This may be due to their scoring system, as they considered excellent response if there was 75–100% decrease in wart size as compared to a full disappearance (100%) in our study. Furthermore, it was much lower than other studies that reported more than 90% clearance [ 15 ]. This can be elucidated by the dissimilar concentration of the combined drugs.…”
Section: Discussioncontrasting
confidence: 55%
“…Combinations of drugs have proven useful in the treatment of HPV-induced warts. [3] Independent of such speculations, there is hope that further optimized prodrugs of AZT for the treatment of infections with DNA viruses exist, and that our results will stimulate work leading to the identification of them.…”
Section: Discussionmentioning
confidence: 91%
“…Given the wealth of clinical data on AZT, it is reasonable to assume that adverse side effects are unlikely to become unsurmountable hurdles to the clinical use of this compound, perhaps in the form of combination therapy, as commonly practiced against HIV. Combinations of drugs have proven useful in the treatment of HPV‐induced warts [3] . Independent of such speculations, there is hope that further optimized prodrugs of AZT for the treatment of infections with DNA viruses exist, and that our results will stimulate work leading to the identification of them.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations